A MODEL OF ENGLISH TEACHING MANAGEMENT OF THE ECCLESIASTICAL SECONDARY SCHOOLS AND THE PUBLIC SCHOOL IN KHON KAEN PROVINCE - Kammasuddho, Phramaha Samran (Journal of Buddhist Education and Research (JBER), 2020)
The purpose of this research was to study a model of the English teaching management in the ecclesiastical secondary schools and public school in Khon Kaen province and to develop the English communication skills in the ecclesiastical secondary schools and public school in Khon Kaen province. The results of this research was found that the English teaching model used in the highest level was questioning, followed by lecturing in the lower level. The least level of using the English teaching model was graphic diagrams and projects. Problems of English teaching in the ecclesiastical secondary schools and public school in Khon Kaen province were about teachers, learners, modern equipments, etc. The solution to those problems were tutorial, training in the fourfold skill, creation of qualitative teaching media, etc. The result of analyzing the progress in the learners’ English communication skills was found that the grades after learning are higher than that before learning of a statistical significance at the level of 0.05.